Ethical Practice in Telepsychology. (August 2015) - Gamble, Nicholas; Boyle, Christopher; Morris, Zoe A
<x xml:space="preserve">Abstract</x> Objective Telepsychology has the potential to revolutionise the provision of psychological service not only to those in remote locations, or with mobility issues, but also for those who prefer flexible access to services. Rapid developments in internet communications technology have yielded new and diverse methods of telepsychology. As a result, ethical regulatory and advisory guidelines for practice have often been developed and disseminated reactively. This article investigates how the core ethical principles of confidentially, consent and competence are challenged in telepsychological practice. Method Through the application of existing ethical standards, advances in communications technology are considered and their ethical use in psychological contexts explored. Conclusion It is expected that psychologists will have basic competencies for the use of everyday technology in their practice. However, the use of internet communications technology for telepsychology has created new opportunities and challenges for ethical practice. For example, telepsychology is geographically flexible, but there can be privacy concerns in cross‐border information flow. Psychologists who engage in telepsychology require a particularly thorough understanding of concepts such as data mining, electronic storage, and internet infrastructure. This article highlights how existing technology and communication tools both challenge and support ethical practice in telepsychology in an Australian regulatory context.